An Ecocriticism of One Selected IsiXhosa Folktale as Part of Oral Literature - Diko, Mlamli (Journal of Language and Literature, 2024)
Whereas amaXhosa literature continues to receive scholarly consideration, there is a deficit regarding scrutinizing amaXhosa folktales, particularly through the ecocriticism theory. As a result of this, there is an asymmetrical understanding of how ecosystems can be integrated into amaXhosa literature to advance the meaning of folktales in addition to the reality that folktales contain didactic and pedagogical components. It stands to reason, therefore, to channel heightened deliberation on amaXhosa folktales as part of oral literature. Given this fact, this article aims to examine how one selected amaXhosa folktale fuses ecological features into its pursuits to promote educational understanding among children and adults. Over and above this, the aim is to demonstrate how important it is to heed the instructional values of those with wisdom as it is pertinent in this particular folktale. The objective is to underline that amaXhosa folktales, as part of oral literature, continue to be applicable and as a result, they ought to be uncovered in the arena of scholarly discourse. The selected folktale, UNtando noNontando (Ntando and Nontando) is appreciated herein as a primary source of data, while ecocriticism is applied as a theory of interpretation and analysis. The findings and discussions indicate that this particular folktale advances the idea that humans, nature and animals are symbiotic and interactive in the environmental setting. Nevertheless, humans ought to respect the territories of animals and nature in a bid to create a proportioned society. The concluding remarks of this article present possible avenues for future scholarly discourses.